Identification of a Src kinase SH3 binding site in the C‐terminal domain of the human ErbB2 receptor tyrosine kinase. Issue 12 (8th May 2014) - Bornet, Olivier; Nouailler, Matthieu; Feracci, Michaël; Sebban-Kreuzer, Corinne; Byrne, Deborah; Halimi, Hubert; Morelli, Xavier; Badache, Ali; Guerlesquin, Françoise
Abstract : Overexpression of the ErbB2 receptor tyrosine kinase is associated with most aggressive tumors in breast cancer patients and is thus one of the main investigated therapeutic targets. Human ErbB2 C‐terminal domain is an unstructured anchor that recruits specific adaptors for signaling cascades resulting in cell growth, differentiation and migration. Herein, we report the presence of a SH3 binding motif in the proline rich unfolded ErbB2 C‐terminal region. NMR analysis of this motif supports a PPII helix conformation and the binding to Fyn‐SH3 domain. The interaction of a kinase of the Src family with ErbB2 C‐terminal domain could contribute to synergistic intracellular signaling and enhanced oncogenesis. Abstract : Polyproline motif included in ErbB2 C‐terminal domain. Fyn SH3 binds ErbB2 PPII motif. ErbB2 C‐terminal domain interacts with a Src kinase.